Estudo fitoquímico e de atividades biológicas das folhas de Salacia grandifolia; síntese e avaliação da citotoxicidade de derivados do friedelinol - Leila Renan Oliveira (2022)
The phytochemical study of Salacia grandifolia hexane leaf extract resulted in the isolation and characterization of eight constituents. The isolation yielded a new pentacyclic triterpene, 28-hydroxyfriedelane-3,15-dione (SG8) and seven known friedelane triterpenes: friedelan-3-one (SG1), friedelan-3β-ol (SG2), friedelane-3,15-dione (SG3), 15α-hydroxyfriedelan-3-one (SG4), 28-hydroxyfriedelan-3-one (SG5), 30-hydroxyfriedelan-3-one (SG6) and 29-hydroxyfriedelan-3-one (SG7). The synthesis of eight new triterpene esters was also carried out, starting from the isomers friedelan-3α-ol e and friedelan-3β-ol. The study of biological activities consisted in the evaluation of antiviral activity against the murine coronavirus and the antibacterial activity against S. aureus and methicillin-resistant S. aureus (MRSA) for the isolated triterpenes (SG1-SG8) and three extracts (hexane, chloroform and ethyl acetate extracts of S. grandifolia leaves). In addition, the cytotoxic activity of four triterpenes (SG3, SG5, SG6 and SG8) and five synthesized esters were evaluated against THP-1 and K-562 leukemia cell lines. Two extracts (hexane and ethyl acetate) and the compounds SG5 and SG8 exhibited moderate to high antiviral activity, with emphasis on SG5, which presented EC50 = 3.125 µM. Neither the triterpenes nor the extracts showed antibacterial activity against S. aureus or MRSA. The esters and compounds tested showed low cytotoxic activity against THP-1 and K-562 leukemia cell lines.